Face two face: (Cambridge University Press, 2006)
The presentation and practice of vocabulary and grammar are of equal importance and there is a strong focus on listening and speaking with an emphasis on 'real world' language for social situations. The listening and reading material provides fresh new angles on universal topics and students are given numerous opportunities to practise new language through a wide variety of communicative activities, many of which are personalised. face2face is also fully compatible with the Common European Framework of Reference for Languages and gives students regular opportunities to evaluate their progress. Full mapping to the CEF is available online, as well as in the relevant Teacher's Book. Each self-contained lesson is easily teachable off the page with minimal preparation. The Teacher's Books contain optional photocopiable resources and tests, ensuring that the course can be tailored to the needs of different classes. Each level provides approximately 80 hours of core teaching material, which can be extended to 120 hours with the inclusion of the photocopiable resource material and extra ideas in the Teacher's Book (60 hours extendable to 90 for the Starter level). The Student's Books are packaged with a free CD-ROM/Audio CD that offers hundreds of extra practice activities, video sequences, recording capability, customisable tests and much more. The face2face Elementary Student's Book CD-ROM/Audio CD won the ESU President's Award 2005 for the best use of new technology in ELT. The edition is based on the communicative approach, and drawing on the best of current thinking and practice, face2face prepares students for real world communication.